A Miniature Fuel Cell with Monolithically Fabricated Si Electrodes: Application of Au-Pd-Pt Multilayer Catalyst. Issue 15 (1st January 2019) - Shirai, Ryo; Irita, Masaru; Kurose, Tomohiro; Vasiljevic, Natasa; Hayase, Masanori
Abstract : Our first miniature fuel cell prototype with a novel Au-Pd-Pt catalyst successfully demonstrated power generation. In order to reduce amount of platinum group metals and obtain high CO tolerance, electrochemical atomic layer deposition (ALD) of Pd and Pt on porous Au was proposed for the catalyst formation. The electrochemical ALD was realized by surface limited redox replacement (SLRR) process of underpotentially deposited hydrogen (H-UPD-SLRR). The amount of the deposit and catalytic activity of Au-Pd-Pt structures were tested and optimized on Au wire. A performance of a miniature fuel cell prototype with a porous Au layer formed on a Si chip with several Pd monolayers and Pt sub-monolayer coverage was examined. Pd and Pt loadings were estimated to be 101 μg/cm 2 and 10 μg/cm 2, respectively. Though the peak power was poor around 100 mW/cm 2, no performance drop with 100 ppm CO was observed and results were promising as the first prototype.